(untitled) (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: Duck virus enteritis is a severe viral disease that kills ducks and swans worldwide. The clinical manifestations, gross pathology, molecular detection, and characterization of the duck virus enteritis virus (DVEV) in Australian black swans at a safari park in Bangladesh were described in this case report. Materials and Methods: On a safari park in Bangladesh, an Australian black swan flock exhibited clinical signs of anorexia, greenish watery diarrhea, increased thirst, partial paralysis, and death. Postmortem examinations of deceased swans revealed extensive pathological abnormalities in the trachea, liver, and spleen. To isolate DVEV, a viral inoculum produced from the liver and spleen of dead swans was implanted into 9–13-day-old embryonated duck eggs via the chorioallantoic membrane (CAM) route. DVEV was confirmed using a polymerase chain reaction (PCR) assay. Phylogenetic analysis was used to determine the genetic relationship between the DVEV isolates from Australian black swans, and 16 DVEV isolates previously described in the GenBank. Results: Hemorrhage was noted in the annular ring of the trachea, as well as an enlarged and hemorrhagic liver and spleen. The PCR assay amplified a 446-bp fragment of the DVEV DNA polymerase gene in the liver, spleen, and CAM homogenates. The phylogenetic analysis found that the DVEV isolates from swans were comparable to those from Bangladesh, India, Vietnam, China, Germany, the USA, and Egypt. Conclusion: According to the findings of this study, the DVEV was the cause of illness and mortality in an Australian black swan flock. J. Adv. Vet. Anim. Res., 8(4): 557-562, December 2021 http://doi.org/10.5455/javar.2021.h545